Optimizing Process and Design of Die with CAE on the Car - Su Chunjian; Xie Zhendong; Guo Sumin; Tian Heqiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The traditional mould design method mainly relies on the experience, it needs repeated debugging and processing which prolongs the mould development time and increases the mould manufacturing cost. The modern advanced mold design uses the finite element analysis software to do numerical simulation on the forming process of the die and optimizes the parameters of the mould which is very helpful for improving the precision of mould design.Take the rear quarter panel of car as an example, using the DYNAFORM finite element software to do simulation on blank forming process to control the springback after unloading on the shallow and deep parts and design the mould of rear quarter panel based on optimization results, so as to improve the accuracy of the mold and reduce the mold development time and the mould cost.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3256